Implementation of STEM-Integrated Guided Inquiry Learning to Improve Students' Mathematical Communication Skills - Erviana, Neriza Fauziah; Noer, Sri Hastuti; Triana, Mella (Jurnal Pendidikan Matematika dan Sains, 2025)
Mathematical communication skills are a component of higher-order thinking skills that are important in 21st-century learning and support complex mathematical problem-solving. The purpose of the study was to determine the effect of the implementation of STEM-integrated guided inquiry learning on improving students' mathematical communication skills. his study used a pretest-posttest control group design and a quantitative, quasi-experimental methodology. All eighth-grade students from SMPN in Bandar Lampung, who were divided among eight classes for the 2024/2025 academic year, made up the study's population. Using a purposive sampling strategy, the research sample was chosen from two classes: class 8.1, which had 28 students as the experimental class, and class 8.2, which had 24 students as the control class. Based on the results of statistical analysis with the Mann-Whitney U test, it was concluded that the improvement in mathematical communication skills of students who participated in STEM-integrated guided inquiry learning was higher than the improvement in mathematical communication skills of students who participated in the traditional learning paradigm. Thus, the implementation of STEM-integrated guided inquiry learning can improve students' mathematical communication skills.